Pituitary volumes are changed in patients with conversion disorder - Atmaca, Murad; Baykara, Sema; Mermi, Osman; Yildirim, Hanefi; Akaslan, Unsal (Springer, 2016)
Our study group previously measured pituitary volumes and found a relationship between somatoform disoders and pituitary volumes. Therefore, in conversion disorder, another somatoform disorder, we hypothesized that pituitary gland volumes would be reduced. Twenty female patients and healthy controls were recruited to the present investigation. The volumes of the pituitary gland were determined by using a 1.5 Tesla magnetic resonance scanner. We found that the pituitary gland volumes of the patients with conversion disorder were significantly smaller than those of healthy control subjects. In the patients with conversion disorder but not in the healthy control group, a significant negative correlation between the duration of illness and pituitary gland volume was determined. In summary, in the present study, we suggest that the patients with conversion disorder have smaller pituitary volumes compared to those of healthy control subjects. Further studies should confirm our data and ascertain whether volumetric alterations determined in the patients with conversion disorder can be changed with treatment or if they change over time.
Keywords: Pituitary gland; Volumetric; Conversion disorder; MRI